2015
DOI: 10.3171/2014.11.jns13680
|View full text |Cite
|
Sign up to set email alerts
|

The utility of preoperative diffusion tensor imaging in the surgical management of brainstem cavernous malformations

Abstract: abbreviatioNs BSCM = brainstem CM; CM = cavernous malformation; CST = corticospinal tract; DTI = diffusion tensor imaging; DTT = diffusion tensor tractography; FA = fractional anisotropy; ICP = inferior cerebral peduncle; ML = medial lemniscus; MLF = medial longitudinal fasciculus; mRS = modified Rankin Scale. submitted April 9, 2013. accepted November 18, 2014. iNclude wheN citiNg Published online January 9, 2015; DOI: 10.3171/2014.11.JNS13680. disclosure The authors report no conflict of interest concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…Once surgery has been decided on, WMT can aid the selection of the safest approach corridor, particularly when choosing from the multitude of different approaches that are now described for each region of the brainstem (Abla et al, 2011, Essayed et al, 2017, Flores et al, 2015). Also, exploiting the high negative predictive value of WMT at the level of the brainstem, a more radical resection strategy can be safely adopted if major tracts are shown to be spared by the tumor.…”
Section: Infratentorialmentioning
confidence: 99%
“…Once surgery has been decided on, WMT can aid the selection of the safest approach corridor, particularly when choosing from the multitude of different approaches that are now described for each region of the brainstem (Abla et al, 2011, Essayed et al, 2017, Flores et al, 2015). Also, exploiting the high negative predictive value of WMT at the level of the brainstem, a more radical resection strategy can be safely adopted if major tracts are shown to be spared by the tumor.…”
Section: Infratentorialmentioning
confidence: 99%
“…The preoperative anatomical definition of tracts and nerve pathways is performed using DTI tractography. [16][17][18][19][20] However, some studies have found no relevant prognostic value of the DTI or tractography findings. In addition, it is difficult to accurately navigate the tracts reconstructed with tractography even when they are well preserved.…”
Section: Discussionmentioning
confidence: 99%
“…94 MRI also allows functional imaging of primary sensorimotor, speech, and visual cortical areas, and their white matter connectome by diffusion tensor imaging, which has enhanced surgical planning. 27,85 New MRI techniques of quantitative susceptibility mapping (QSM) and dynamic contrast enhanced quantitative perfusion (DCEQP) have been developed to measure iron deposi-tion and vascular permeability in CAs 67 (Fig. 3), and are being assessed as potential biomarkers of clinically relevant disease activity.…”
Section: Fig 1 Amentioning
confidence: 99%
“…38,75 Skull base approaches can facilitate resection of brainstem lesions. 73 It is believed that technical adjuncts, such as image guidance, 27,105 neurophysiological monitoring, 112 and laserassisted technique, 18 improve the outcome of resection strategies when used in eloquent areas; however, there are limited controlled studies to support specific modalities. Severe disability may occur as a result of recurrent hemorrhages as well as surgery in deep eloquent locations and the brainstem, raising a real controversy about the timing and threshold for surgical decisions vis-à-vis prior functional status.…”
Section: Surgical Opportunities and Challengesmentioning
confidence: 99%